(untitled) (Indian Journal Of Clinical Practice, 2025)
Cystic degeneration of cervical lymph nodes is the most accepted theory for occurrence of lateral cervical cyst. It is commonly found in the anterior triangle of the neck, anterior to the upper third of the sternocleidomastoid. Clinical examination, imaging modalities, such as ultrasonography, computed tomography (CT) and magnetic resonance imaging (MRI), and fine needle aspiration cytology (FNAC), are useful investigations to establish the diagnosis. Surgical excision of these lesions is reasoned curative in most of the cases. Authors report a case of lateral cervical cyst which was successfully operated.